2021
DOI: 10.1002/pssa.202100512
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Performance Analysis of Highly Efficient Copper Indium Gallium Selenide Solar Cell with Cu2O Hole Transport Layer Using Solar Cell Capacitance Simulator in One Dimension

Abstract: Herein, the widely available and cheapest cuprous oxide (Cu2O) as hole transport layer (HTL) is proposed to improve the performance of thin‐film copper indium gallium selenide (CIGS) solar cell. Solar Cell Capacitance Simulator in One Dimension (SCAPS‐1D) is utilized to design and study output characteristics of the modeled photovoltaic (PV) cell. A comparison between the proposed cell with Cu2O HTL and the reference CIGS solar cell is presented. The PV performances of CIGS solar cells are analyzed by changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Thus, the performance of the proposed hetero-structure can be realized by analyzing the lattice mismatch percentage. In this study, lattice mismatch δ (%), which is an interface feature defining factor, in the grown film on the substrate can be calculated using equation (4) as [ 43 , 52 , 64 , 65 ]. where a s is the lattice constant of the substrate on which an epitaxial layer is grown and the a e is the lattice constant of a layer.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the performance of the proposed hetero-structure can be realized by analyzing the lattice mismatch percentage. In this study, lattice mismatch δ (%), which is an interface feature defining factor, in the grown film on the substrate can be calculated using equation (4) as [ 43 , 52 , 64 , 65 ]. where a s is the lattice constant of the substrate on which an epitaxial layer is grown and the a e is the lattice constant of a layer.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the doping density of 10 15 cm –3 , PCE, V oc , and FF are enlarged with a further growing SnS doping level. The generation of more charge carriers with expanding doping concentration density in the absorber improves the cell’s performances. ,, It can also be seen that J sc is approximately similar up to the carrier density of 5 × 10 16 cm –3 and then is slightly diminished with rising doping level. The minor degradation of J sc at the high doping level may be due to further creation of hole trap sites through p-type absorber by adding more acceptor impurity, , consequently enhancing the recombination between the created hole trap states and photogenerated electrons according to the Coulomb force. , Herein, a carrier density of 5 × 10 16 is preferred as the optimized absorber doping level for the proposed SnS-based TFSC by considering the manufacturing expense and admirable performance.…”
Section: Resultsmentioning
confidence: 91%
“…The outputs detected in this work are decently consistent with the PV behaviors described in preceding works. 45,82,84 It is also found that the variations of the output parameters are not significant for an ETL thickness less than 0.06 μm. On the other hand, insufficient photoinduced carriers, owing to a lesser extent of radiance reaching the absorber across the thick ETL, may result in a slight decrease in J sc , thereby declining the conversion efficiency to some extent at the thick ETL.…”
Section: Effects Of Etl Thickness and Doping Concentration On Pv Outputsmentioning
confidence: 86%
“…The minor current due to poor photo‐generated carriers with the thicker buffer results this PV behaviors 87,88 . A reduced extent of short wavelength photons may derive to the absorber with increasing the buffer thickness 88–90 . Moreover, the recombination of few photo‐induced electrons and holes produced during photon absorption by the absorber with defects at buffer/absorber interface before going to front contact results in the slight diminution in efficiency at the thick buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…87,88 A reduced extent of short wavelength photons may derive to the absorber with increasing the buffer thickness. [88][89][90] Moreover, the recombination of few photo-induced electrons and holes produced during photon absorption by the absorber with defects at buffer/absorber interface before going to front contact results in the slight diminution in efficiency at the thick buffer layer. Therefore, a thin buffer layer is inhibited to realize noteworthy PV outputs.…”
Section: Impacts Of Thickness and Doping Concentration Of Ws 2 Buffer...mentioning
confidence: 99%